2008
DOI: 10.1177/039463200802100424
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity and Anti-Biofilm Effect of Chitosan against Strains of Streptococcus Mutans Isolated in Dental Plaque

Abstract: Streptococcus mutans is the major cause of dental plaque and is often associated with biofilm formation. The aim of this study is to evaluate the activity of a hydrosoluble derivative of chitosan against S. mutans biofilms in vitro and in vivo. Strains of S. mutans were isolated from the dental plaque of 84 patients enrolled in the study. The antibacterial activity of chitosan was determined by broth microdilutions. The effect of chitosan at different concentrations and exposure times on S. mutans biofilms at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 17 publications
2
23
0
1
Order By: Relevance
“…Although chitosan has also bactericidal properties, the MIC values of chitosan for S. mutans have been reported to range from 500 to 2,000 μg/mL −1 , 17,18) . Despite of this, MIC value of CuChNP against S. mutans is comparable to that reported for silver nanoparticles (50-222 μg/mL −1 ) or traditional oral antibacterials such as chlorhexidine (1,250 μg/ mL −1 ) 19,20) .…”
Section: Discussionmentioning
confidence: 99%
“…Although chitosan has also bactericidal properties, the MIC values of chitosan for S. mutans have been reported to range from 500 to 2,000 μg/mL −1 , 17,18) . Despite of this, MIC value of CuChNP against S. mutans is comparable to that reported for silver nanoparticles (50-222 μg/mL −1 ) or traditional oral antibacterials such as chlorhexidine (1,250 μg/ mL −1 ) 19,20) .…”
Section: Discussionmentioning
confidence: 99%
“…The biopolymer is easily catalyzed to oligosaccharides by various biological enzymes, and is considered biodegradable (12); thus, can be absorbed by the body. Previous studies have demonstrated that chitosan not only has immunoregulatory efficacy, but also a naturally broad spectrum of antibacterial activity that enables the inhibition of biofilm formation (11,13,14). …”
Section: Introductionmentioning
confidence: 99%
“…Despite fluoride being effective against dental plaque formation, high levels of fluoride are cytotoxic [7, 8]. Thus, many attempts have been made to search for an effective agent to prevent dental plaque formation [9, 10]. Recently, several natural products that are derived from herbs, such as Rosmarinus officinalis , Mentha longifolia L., Aralia continentalis, and Curcuma longa L. , have also been studied for their ability to inhibit the formation of dental plaque [1114].…”
Section: Introductionmentioning
confidence: 99%